Eye Infections (Homoeopathy for All, 2023)
Eye infections are a common  medical presentation and can range  in severity from being relatively  mild and self-limiting to potentially  causing serious vision-threatening  complications. While many eye  infections tend to resolve on their  own, some have the potential to lead  to corneal scarring or even permanent  blindness. Prompt diagnosis and  appropriate treatment are essential  for preventing complications and  preserving good vision.
Keywords: Infections; Eye